A study on perception of muslims towards Islamic estate planning: a case study in Kemaman / Muhammad Shahir Aiman Alias - Alias, Muhammad Shahir Aiman (Faculty of Business Management, 2018)
Whenever a person dies, the assets and properties of the deceased will be distributed to the peoples who entitle for it such as to the family members. It requires proper estate management to ensure that the deceased's properties will be distributed without arising any dispute during the process. Islamic estate planning plays an important role in giving guidance for asset redistribution process as it is parallel with the principles of Shariah that is to ensure equality. Due to that, this study had been conducted to investigate the factors that influence the perception of Muslims towards Islamic estate planning since the amount of frozen assets and unclaimed estate in our country is high. Primary data had been collected by distributing the questionnaires to the sample consist of 100 respondents from the Muslims living in Kemaman. The sampling method that been used for this study was convenience sampling where the sample was drawn from the population which is close to hand. Meanwhile, independent variables of this research are knowledge, attitude, subjective norms and religiosity while perception towards Islamic estate planning as the dependent variable. The data collected will be analysed by using Statistical Package of Social Sciences (SPSS). The findings of this research showed that knowledge and attitude had a significant and positive relationship with the perception of Muslims toward Islamic estate planning practises. The results from this study may be used to increase the practices of Islamic estate planning among Muslims, especially in Malaysia.